RETRACTED: A balanced view of digital transformation in environmental education - Kurpayanidi Konstantin; Khamdamova Shokhida; Ergashev Dilmurod; Nishonov Usmonkhon; Kholmatova Dilorom; Khoshimov Akhrorjon (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001